Chapter 6: X-Ray diffraction and focal construct technology - Rogers, Keith; Evans, Paul (CRC Press, 2018)
This chapter examines the background and practice of X-ray diffraction (XRD) and considers this phenomenon principally in the context of X-ray-based security screening. The focus will be upon the practical aspects of XRD as many texts already provide comprehensive descriptions of the relevant theoretical background and that of the closely associated area of crystallography. X-ray diffraction and its development from simple materials identification to dynamic imaging will be considered, followed by a similar view of aviation screening. Subsequently, a new approach to the harvesting of diffraction signatures (Focal Construct Technology) will be introduced and consequent potential applications summarised.